STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMA AN-NUR BULULAWANG MALANG - Yusuf Rizaldi; Nur Hasan; Mutiara Sari Dewi (VICRATINA, 2021)
The head in an instruction assumes a vital part to accomplish the ideal instructive objectives, should truly dominate authoritative administration, what procedures will be utilized to propel the establishment held, should have the option to turn into a top chief who is prepared to contend with different schools, become a main thrust the interaction of instructive change in giving trust and power to all training work force. As a school head, he should be a good example in the school organization, from that the chief should have a reliable mentality, obligation, have solid and savvy standards so he isn't self-assertive and just uses his situation to subordinates, along these lines making the main an individual who can be regarded and appreciated and furthermore be a good example in completing all exercises. The accomplishment of the chief can likewise be seen from how the techniques utilized in driving and building responsibility, joining the right vision and mission, and furthermore overseeing assets that help and accomplish objectives. In fostering the nature of school training, directors should have ideas and have experience that they are really equipped for doing their obligations as propelling the school. The reason for this examination is to depict how the nature of training at SMA An-Nur Bululawang and the school's coconut administration procedure in working on the nature of instruction at SMA An-Nur Bululawang. Kata Kunci: Strategi, Kepala Sekolah, Mutu Pendidikan